Wastophobia: the driver of e-waste management - antecedents and consequences - Muhammad Wasif Hanif; Muhammad Wasif Hanif; Muhammad Nawaz; Hui Wang (Frontiers in Psychology, 2025)
The rapid growth of technological advancements is boosting planned obsolescence behavior, subsequently reducing the lifecycle of electronic products, and raising electronic waste (e-waste) concerns globally. Considering this dilemma, this study aims to explore the antecedents and consequences of wastophobia to promote sustainable consumption behavior, mitigate e-waste, and enhance environmental performance. Data were collected from the electronics industry consumers (n = 302) and analyzed through structural equation modeling via SPSS and AMOS-26. The results found two fundamental antecedents of wastophobia, including awareness of wasteful consumption and awareness of consequences, which are interrelated but distinct constructs. Together, these determinants significantly cultivated wastophobia in consumer behavior. Moreover, heightened wastophobia has impacted significantly positively on multiple behavioral outcomes, including creative performance, moral courage, and pro-environmental behavior (except for consumer advocacy). The elevated wastophobia rooted in emotions, such as dismay, culpability, and decrepit significantly improves the usability cycle of products, reduces planned obsolescence, e-waste, and consequently enhances environmental performance. This study suggests stakeholders (consumers, organizations, governments, and society) to promote wastophobia culture at societal (community and organizations), national, and global levels to minimize e-waste.